Molecular insight into RNA polymerase I promoter recognition and promoter melting - Sadian, Yashar; Baudin, Florence; Tafur, Lucas; Murciano, Brice; Wetzel, Rene; Weis, Felix; Müller, Christoph W. (Nature Communications, 2019)
RNA polymerase I (Pol I) assembles with core factor (CF) and Rrn3 on the rDNA core promoter for transcription initiation. Here, we report cryo-EM structures of closed, intermediate and open Pol I initiation complexes from 2.7 to 3.7 Å resolution to visualize Pol I promoter melting and to structurally and biochemically characterize the recognition mechanism of Pol I promoter DNA. In the closed complex, double-stranded DNA runs outside the DNA-binding cleft. Rotation of CF and upstream DNA with respect to Pol I and Rrn3 results in the spontaneous loading and opening of the promoter followed by cleft closure and positioning of the Pol I A49 tandem winged helix domain (tWH) onto DNA. Conformational rearrangement of A49 tWH leads to a clash with Rrn3 to initiate complex disassembly and promoter escape. Comprehensive insight into the Pol I transcription initiation cycle allows comparisons with promoter opening by Pol II and Pol III., RNA polymerase I (Pol I) catalyses the transcription of pre-ribosomal RNA and for transcription initiation Pol I assembles with core factor and Rrn3 on the rDNA core promoter. Here the authors provide insights into the molecular mechanism of promoter opening by Pol I by determining the cryo-EM structures of two closed, two intermediate and two open Pol I pre-initiation complexes.
Gesehen am 19.02.2020